Anti-angiogenic-specific adverse events in patients with non-small cell lung cancer treated with nintedanib and docetaxel. Issue 2 (November 2015) - Reck, Martin; Mellemgaard, Anders; von Pawel, Joachim; Gottfried, Maya; Bondarenko, Igor; Cheng, Ying; Zarogoulidis, Kostas; Luft, Alexander; Bennouna, Jaafar; Barrueco, José; Aboshady, Hesham; Hocke, Julia; et al.
Highlights: The combination of nintedanib/docetaxel was evaluated in LUME-Lung 1. Adverse events (AEs) seen with existing anti-angiogenic agents were evaluated. AEs associated with other agents were less pronounced with nintedanib + docetaxel. Abstract: Objectives: LUME-Lung 1 was a randomized, placebo-controlled, Phase III trial investigating nintedanib + docetaxel versus placebo + docetaxel in patients with advanced NSCLC progressing after first-line chemotherapy. Progression-free survival was significantly improved with nintedanib + docetaxel in the overall population and overall survival was significantly improved in the pre-specified analysis of patients with adenocarcinoma. We evaluated the frequency of characteristic adverse events (AEs) commonly seen with existing anti-angiogenic agents. Materials and methods: The incidence and intensity of AEs were evaluated in all patients who received at least one dose of study medication ( N  = 1307) and for the two main histologies: adenocarcinoma ( n  = 653) and squamous cell carcinoma (SCC; n  = 553). AEs of special interest were analyzed by category, preferred term, and worst CTCAE grade and included perforation, hypertension, bleeding, thromboembolic events, and skin disorders. Results and conclusion: The incidence of patients with all-grade gastrointestinal (GI) perforations was low and balanced between arms (0.5% in both) and across histologies; the incidence of non-GI perforations was 1.2% with nintedanib + docetaxel versus 0.2% with placebo + docetaxel. The incidence of some events was higher with nintedanib + docetaxel versus placebo + docetaxel; hypertension (3.5% vs 0.9%), rash (11.0% vs 8.1%), and cutaneous adverse reactions (13.0% vs 10.7%). Rash and cutaneous adverse reactions were predominantly Grade 1–2 with both treatments. The incidence of all-grade bleeding was also slightly higher in nintedanib + docetaxel-treated patients (14.1% vs 11.6%) driven by between-treatment differences in the SCC subpopulation; most events were Grade 1–2. The proportion of patients with a thromboembolic event was low and comparable between arms for all grades (5.1% vs 4.6%) and Grade ≥3 (2.1% vs 3.1%). Safety evaluation of the LUME-Lung 1 study showed that the frequency of AEs commonly associated with other anti-angiogenic agents was lower with nintedanib + docetaxel. Survival benefits from addition of nintedanib to docetaxel in patients with adenocarcinoma after first-line therapy can be achieved alongside a manageable safety profile.